Effects of Elevated Carbon Dioxide Concentrations on Broiler Chicken Performance from 28 to 49 Days - Purswell, J.L.; Davis, J.D.; Luck, B.D.; Kim, E.J.; Olanrewaju, H.A.; Kiess, A.S.; Branton, S.L. (International Journal of Poultry Science, 2011)
Improvements in modern broiler housing have substantially reduced air leakage, making proper operation of ventilation systems critical to maintaining a suitable environment. Fuel prices have increased in recent years, leading to reduced minimum ventilation in order to conserve fuel which increases carbon dioxide (CO2) concentrations within the house. Four trials were conducted to assess the effects of increased CO2 concentrations on birds aged 28 to 49 days. Each trial used 300 straight-run broilers placed in environmentally controlled rooms where CO2 concentrations were maintained with no added CO2 (control), 2500 ppm at all times, 2500 ppm (day) and 4500 ppm (night), or 2500 ppm (day) and 6500 ppm (night) from 28 to 42 days. No differences in live production (body weight, body weight gain, feed intake and feed conversion) or processing yields were observed. Analysis of ventilation rates to maintain the test conditions for a commercial broiler house showed that while supplemental heat requirements are lower with reduced ventilation needed to maintain either 4500 or 6500 ppm, the associated ventilation rates are inadequate for moisture removal.